ENHANCING CRITICAL THINKING SKILLS THROUGH ANDROID-ASSISTED VIRTUAL PHYSICS LEARNING: A FOCUS ON HOTS DEVELOPMENT - Mardiana, Nana; Maulina, Bania; Mardiani, Nani; Sabar, Sumiyyah; Collantes, Leila M. (Jurnal Ilmiah Ilmu Terapan Universitas Jambi, 2025)
This study investigates the effectiveness of Android-assisted virtual physics learning developed using Smart Application Creator in enhancing students' critical thinking skills during the study of optical material in high school. The novelty of this research lies in its integration of mobile-based virtual learning environments with a targeted emphasis on Higher Order Thinking Skills (HOTS) a crucial competency in 21st-century education. While prior studies have explored virtual learning media in science education, few have systematically examined their cognitive impact particularly on critical thinking in the context of physics. A quasi-experimental design with a nonequivalent control group was used, and purposive sampling determined the participant pool. Data were collected using validated test instruments designed to assess five core indicators of critical thinking. Statistical analysis through an independent sample t-test at a significance level of α = 0.05 revealed a sig. (2-tailed) value of 0.00, indicating a significant difference between the experimental and control groups. The average N-Gain in the experimental group (0.74) significantly outperformed that of the control group (0.53). The most notable improvements in the experimental group included the ability to evaluate arguments (88.2%), draw conclusions (84.3%), identify assumptions (80.4%), apply deductive reasoning (75.2%), and logically interpret data (65%). These findings demonstrate the pedagogical potential of Android-based virtual media in supporting cognitive development in physics learning. The study provides a foundation for developing scalable, interactive learning tools that align with HOTS frameworks, offering new directions for physics instruction in digitally driven classrooms.